A case report of a rare cardiac complication in novel coronavirus disease. Issue 6 (14th November 2020) - Malekrah, Alireza; Fatahian, Alireza
Abstract: Background: Since late 2019, the outbreak of COVID-19 has rapidly spread worldwide. As it is a newly emerged disease, many of its manifestations and complications are unknown to us. Cardiac involvement and arrhythmias are another aspect of the disease about which very little is known. Case summary: A 71-year-old male patient presented at the Emergency Department complaining of fever, a dry cough, and dyspneoa. He was admitted due to these symptoms suggestive of COVID-19, and a chest CT and PCR test confirmed the diagnosis. During admission, cardiac involvement was detected, i.e. second-degree atrioventricular block with intermittent left bundle branch block (LBBB) which progressed to fixed LBBB and eventually developed into atrial fibrillation/flutter with bradycardia. Both cardiac troponin and echocardiographic findings for detecting myocarditis were negative. We waited 14 days for resolution of atrioventricular block before permanent pacemaker implantation, but the condition still did not improve after the waiting period. Discussion: COVID-19 is mainly a respiratory infection but cardiac involvement is not uncommon in the course of the disease. Arrhythmia, during this infection, seems to be caused by an inflammatory response in the myocardium, electrolyte disturbances, and hypoxia; the course of the disease in our case study shows that the virus can preferentially and irreversibly involve the cardiac conduction system.